Implementasi Kebijakan Sertifikasi Keahlian Teknik Jalan Dan Jembatan Berdasarkan Uu No. 2 Tahun 2017 Tentang Jasa Konstruksi Pada Dinas Bina Marga Dan Bina Konstruksi Provinsi Sumatera Utara - Dasopang, Hasian Negara; Hartono, Budi; Harahap, Dumasari (Mahesa Research Center, 2023)
The implementation of competency certification requirements has not been fully implemented, both for agencies as service users and for business actors as construction service providers, because there are still many employees or workers who do not have competency certificates who are placed as planners and supervisors, or even as technical persons in charge. The formulation of the research problem is how the implementation and the obstacles in implementing the policy of certification of road and bridge engineering expertise based on Law no. 2 of 2017 concerning Construction Services at the Office of Highways and Construction Development of North Sumatra Province. The results of the study show that the Department of Highways and Construction (BMBK) of North Sumatra Province has tried to implement an employee certification policy, but in its implementation it has not been able to fully achieve the expected goals. The obstacle faced in the implementation or implementation is that the BMBK Service does not cooperate with professional certification bodies so that it cannot facilitate employees. It is recommended that the BMBK Office of North Sumatra Province needs to cooperate with professional certification bodies in order to facilitate employees in obtaining the required skill certificates. The employees should show a high commitment to produce the SKTJJ policy because it is very important to improve the quality of development in North Sumatra.